2006
DOI: 10.1111/j.1439-0418.2006.01083.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to silverleaf whitefly, Bemisia argentifolii (Hem., Aleyrodidae), in Gossypium thurberi, a wild cotton species

Abstract: Gossypium thurberi Todaro is a wild cotton species native to Mexico and parts of the southwestern USA. Four years of field studies in California's Imperial Valley revealed consistent very high levels of resistance in G. thurberi against silverleaf whitefly, Bemisia argentifolii Bellows and Perring, an important pest of cotton in many regions of the world. Naturally developing field infestations in plots of G. thurberi were significantly lower than in plots of the commercial cotton cultivars DP 5415, Siokra L23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…In another screening for cotton resistance against B-biotype of B. tabaci, adults, eggs and nymphs were significantly corelated to leaf hairiness, with seasonal variability due to leaf color, shape, and hairiness types (Alexander et al 2004). A brief review by Walker and Natwick (2006) pointed out the mixed and sometimes contradictory results presented in these and other previous studies which associate the two different traits in cotton (smooth-leaf and okra-leaf) with reduced whitefly susceptibility, while in other studies, a slight effect, no effect, or even the opposite effect occurred. All these results together indicate that many morphological plant traits cumulatively contribute to whitefly population fluctuation (Sial et al 2003).…”
Section: Plant Resistance To B Tabaci In Other Cropsmentioning
confidence: 92%
See 2 more Smart Citations
“…In another screening for cotton resistance against B-biotype of B. tabaci, adults, eggs and nymphs were significantly corelated to leaf hairiness, with seasonal variability due to leaf color, shape, and hairiness types (Alexander et al 2004). A brief review by Walker and Natwick (2006) pointed out the mixed and sometimes contradictory results presented in these and other previous studies which associate the two different traits in cotton (smooth-leaf and okra-leaf) with reduced whitefly susceptibility, while in other studies, a slight effect, no effect, or even the opposite effect occurred. All these results together indicate that many morphological plant traits cumulatively contribute to whitefly population fluctuation (Sial et al 2003).…”
Section: Plant Resistance To B Tabaci In Other Cropsmentioning
confidence: 92%
“…Recent field studies in California's Imperial Valley revealed consistent very high levels of resistance against the silverleaf whitefly in Gossypium thurberi Todaro, a wild cotton species native to Mexico and parts of the southwestern USA (Walker and Natwick 2006). However, the mechanisms of this resistance remains an enigma because both choice and no-choice experiments comparing oviposition and nymphal survival among G. thurberi and commercial cotton cultivars did not detect antibiosis or antixenosis (Walker and Natwick 2008).…”
Section: Plant Resistance To B Tabaci In Other Cropsmentioning
confidence: 97%
See 1 more Smart Citation
“…The potential of whiteflies to colonize on a whole plant under no-choice conditions was not fully exploited. However, Walker and Natwick (2006) reported that the wild cotton species Gossypium thurberi showed a high level of resistance in field conditions, with no significant preference for oviposition being detected in no-choice experiments, in which whole plants were covered. Moreover, the plant age/stage used to identify resistant sources and biology studies by different workers is quite variable: e.g.…”
Section: Introductionmentioning
confidence: 96%
“…The cotton genotypes resistant to whitefly were identified by several workers under free choice conditions (Khan et al 2003;Puri et al 1998;Rao et al 1991) with the aim to identify an antixenosis mechanism of resistance among the three listed by Painter (Painter 1951). Under no-choice conditions, considerable attention has been given to detect antibiosis or antixenosis by confining whiteflies on a single leaf (Butter and Vir 1991;Walker and Natwick 2006;Zang et al 2006). The potential of whiteflies to colonize on a whole plant under no-choice conditions was not fully exploited.…”
Section: Introductionmentioning
confidence: 99%